2022
DOI: 10.1111/imj.15628
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 pandemic: end‐of‐life experience in Australian residential aged care facilities

Abstract: Background The COVID‐19 pandemic has significantly impacted on those in Residential Aged Care Facilities (RACFs). This research was undertaken to explore and better understand the effects of the pandemic on the experience of next‐of‐kin and carers who encountered the death of a loved one who resided within a RACF during the pandemic. Methods Prospective single‐centre mixed methods research was undertaken involving telephone interview with next‐of‐kin or carers of reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…34 The reduced face-to-face contact during the pandemic also appeared to take an emotional toll on relatives and surrogates involved in care planning. 30,33,35 Emotions such as denial and shock concerning a loved one's condition (particularly in the case of acute COVID-19 diagnosis) seemed to be triggered by relatives' reduced ability to directly observe changes over time. 30,31 Although synthesis suggests these circumstances can lead to a greater risk of interventional and curative orientated decisions by relatives, 29,30,35 it was found that frequent ongoing involvement of relatives in care planning conversations can help to mitigate these emotions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…34 The reduced face-to-face contact during the pandemic also appeared to take an emotional toll on relatives and surrogates involved in care planning. 30,33,35 Emotions such as denial and shock concerning a loved one's condition (particularly in the case of acute COVID-19 diagnosis) seemed to be triggered by relatives' reduced ability to directly observe changes over time. 30,31 Although synthesis suggests these circumstances can lead to a greater risk of interventional and curative orientated decisions by relatives, 29,30,35 it was found that frequent ongoing involvement of relatives in care planning conversations can help to mitigate these emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Although face-to-face discussions still occurred between care home staff and residents; relatives and surrogates were often involved in these discussions remotely using video or phone calls due to visiting restrictions. 29,31,33,35,36,38 Several benefits resulted from the adoption of remote communication compared to face-to-face discussions, which included easier and more frequent access to relatives, being able to schedule calls and being able to speak concurrently with more relatives. 29,33 Nonetheless, maintenance of an individual and person-centred approach during care planning discussions appeared to be challenged by remote communication.…”
Section: Intervention Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ref. [114] investigated how the COVID-19 pandemic has affected the experiences of next-of-kin and carers who witnessed the death of their loved ones in residential aged care facilities (RACFs). The study revealed that participants and their dying loved ones faced various pandemic-related challenges in RACFs.…”
Section: Palliative Carementioning
confidence: 99%